Developing Android-based English Multimedia in Improving the Skill of Literary Criticism - Ahmadi, Farid; Hapsari, Intan Permata; Artharina, Filia Prima (Universitas Negeri Semarang, 2022)
The vast advancement of technology further encourages the concept of independent learning for every individual in improving their skill in English literary criticism outside the formal education. This study aims at developing and identifying the feasibility of android-based English Multimedia in improving the skill of literary criticism. This research applies ADDIE development model that consists of five stages. The data collecting technique used involves observation, interview, questionnaire, and scale. The data analysis is carried out in the form of qualitative data analysis that is converted into several criteria. The findings present that there is a demand among English tutors and the members of English Community on the development of android-based English Multimedia. The media proposed is deemed valid by material and media experts as it earns the score of 87 and 86 with the category of very feasible. Therefore, in the attempt of improving the skill of literary criticism, android-based English Multimedia can be utilized outside the formal education. The development of technology-based media in the learning of literary criticism is the form of learning media innovation for non-formal education as adjusted to the current development in the digital literary era. The effectiveness of android-based English multimedia can be identified in the upcoming research as the basis in developing media for improving other skills in non-formal education.